Obesity alters adipose tissue response to fasting and refeeding in women: A study on lipolytic and endocrine dynamics and acute insulin resistance - Rossmeislová, Lenka; Krauzová, Eva; Koc, Michal; Wilhelm, Marek; Šebo, Viktor; Varaliová, Zuzana; Šrámková, Veronika; Schouten, Moniek; Šedivý, Petr; Tůma, Petr; Kovář, Jan; Langin, Dominique; et al. (Heliyon, 2024)
Fasting induces significant shifts in substrate utilization with signs of acute insulin resistance (IR), while obesity is associated with chronic IR. Nonetheless, both states substantially influence adipose tissue (AT) function. Therefore, in this interventional study (NCT04260542), we investigated if excessive adiposity in premenopausal women alters insulin sensitivity and AT metabolic and endocrine activity in response to a 60-h fast and a subsequent 48-h refeeding period. Using physiological methods, lipidomics, and AT explants, we showed that obesity partially modified AT endocrine activity and blunted the dynamics of AT insulin resistance in response to the fasting/refeeding challenge compared to that observed in lean women. AT adapted to its own excess by reducing lipolytic activity/free fatty acids (FFA) flux per mass. This adaptation persisted even after a 60-h fast, resulting in lower ketosis in women with obesity. This could be a protective mechanism that limits the lipotoxic effects of FFA; however, it may ultimately impede desirable weight loss induced by caloric restriction in women with obesity.